Developing Instructional Game "Adventure of Word" to Improve Morphological Awareness on Vocational Higher Students - Devi Kuniasari Riyadi; Putu Dian Danayanti Degeng; Esti Junining (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
Morphological awareness (MA) has relation to language development. Most of Informatics students class of 2017 in Politeknik Kota Malang are lack of MA especially in vocabulary and reading comprehension. Therefore, this present study is aimed at developing instructional game “Adventure of Word” to improve morphological awareness. This is Research & Development study which used Lee & Owens’ development model. From the result of expert validation, from media expert it got 96.8% and from media/design expert it got 78.7%. As those results, the product is categorized as ‘valid’. After the product has been validated, the next step is try-out to the students. It got 96.6% which meant the product is classified as ‘excellent’. It can be concluded that the product was well-developed as instructional media to teach morphology explicitly so that can help students to improve their morphological awareness especially in root word, prefix, suffix, and circumfix.